Children customary clothe in Malay head shaving – cukur jambul ceremony for the communal - Idayu Ibrahim, Nor; Ab Aziz, Arba’iyah; Mohamad Kamal Abd Aziz, Mohamad (International Journal of Engineering and Technology, 2018)
The Malay Archipelago, Malay community have a unique tradition and custom that are align to their belief and lifestyle. Head Shaving ceremony is a kind of a ceremony in Malay tradition and custom. This is one of a kind to welcoming the birth of a new baby into the family. Each custom is regarded as unique and special, that has been celebrated for specific purpose that lies in the same Islamic taught and belief. This study aims to discover the children customary clothe in Malay head shaving ceremony or Cukur Jambul that focuses on the Malay tradition. Other than that, it is to document the knowledge with regards to the Malay children starts from baby. This study emphasizes Meyer Schapiroâ€™s on theory of style in the context of artefact or material culture object. The research paper applies the qualitative method due to its flexibility views from the informants, observation is made due to the photos collection during the head shaving ceremony. The Malay was maintaining to use Malay traditional clothe in most of their custom ceremonies until today. All in all, this study will provide invaluable source of references to the Malay custom and culture that benefited the royaltyâ€™s family, researchers, academicians, scholars, students, cultural activist, and museum curators in archiving about the customary clothe during Head Shaving ceremony.Â